Auswahl generativer prozessketten für die herstellung metallischer endprodukte - Karpuschewski, B.; Pieper, H.-J.; Kushnarenko, O. (НТУ "ХПІ", 2010)
The application of generating processes for the creation of metal end-products can only be applied economically with small batch size and geometrically high-complex workpieces. This paper concerns the analytic evaluation of several additive methods and its process chains and compares these with traditional manufacturing technologies regarding the quality, processing time, expenses as well as the complexity of the product. The existing methods of process planning and the assurance of the quality are extended with a focus on the new manufacturing possibilities which can be realized by the application of additive processes.

У даній статті розглядаються питання аналітичної оцінки процесу селективного спікання і його технологічних ланцюжків у порівнянні із традиційними технологіями виробництва. Критеріями порівняння є якість, час обробки, витрати, а також складність геометрії виробу. Існуючі методи планування й забезпечення якості повинні бути доповнені з урахуванням нових можливостей виготовлення виробів, які відкривають генеративні методи. Застосування генеративних технологій для виготовлення металевих кінцевих продуктів економічно обґрунтовано тільки для деталей зі складною геометрією й малим розміром.
Keywords: спікання селективне; якість; продукція; якість